Rapid kinetic evaluation of homogeneous single-site metallocene catalysts and cyclic diene: how do the catalytic activity, molecular weight, and diene incorporation rate of olefins affect each other?. Issue 50 (27th September 2021) - Ali, Amjad; Nadeem, Muhammad; Lu, Jinwei; Moradian, Jamile Mohammadi; Rasheed, Tahir; Aziz, Tariq; Maouche, Chanez; Guo, Yintian; Awais, Muhammad; Zhiqiang, Fan; Quo, Li
Abstract : The kinetics and mechanism of ethylene and 5-ethylidene-2-norbornene copolymerization catalyzed by rac -Et(Ind)2 ZrCl2 were investigated using 2-thiophenecarbonyl chloride. Abstract : The kinetics and mechanism of ethylene and cyclic diene 5-ethylidene-2-norbornene (ENB) copolymerization catalyzed by rac -Et(Ind)2 ZrCl2 /[Ph3 C][B(C6 F5 )4 ]/triisobutylaluminium (TIBA) were investigated using a quench-labeling procedure using 2-thiophenecarbonyl chloride (TPCC). The E/ENB copolymers were characterized by gel permeation chromatography (GPC), differential scanning calorimetry (DSC), scanning electron microscopy (SEM), and 1 H nuclear magnetic resonance (NMR) spectroscopy and sulfur analysis. To reduce the errors of the ethylene–diene copolymerization for the kinetics study, we selected E/ENB with steric and electronic features that permit us to elucidate the metallocene catalyst behavior against dienes. A quantitative approach of catalyst speciation, stereodynamics, and micro-kinetics assisted the resolution of mechanistic problems, such as the elastomeric synthesis of ethylene propylene diene monomer rubber (EPDM), the catalyst resting state nature, and how much ion-pairing occurs during polymerization. We report here the precise observation of metal–polymer species, explanation of the dynamics of their initiation, propagation, and termination, and ethylene ENB copolymer development. An approach based on acyl chloride was used to selectively quenched transition metal–polymer bonds to evaluate the polymeric catalyst in terms of its reaction rate, R p, propagation rate content, k p, and mole fraction of active centers. It is noted that the decline in catalytic activity in the range of 1800 s, and the active center [Zr]/[*C] fraction significantly increased during the initial 1000 s and then tended towards a steady figure of 86%. It is suggested that nearly complete initiation of all olefins catalysts can be obtained after a sufficiently extended reaction. The quick increase in active sites in the first stage can be described by the immediate initiation of active sites positioned on the surfaces of catalyst particles. The initial polymerization rate, R p, is high and the crystalline properties of the E/ENB copolymer are low due to the greater incorporation of ENB in the polymer backbone, and later the polymerization reaction rates remained stable with a lower mol% of ENB. The melting temperature ( T m ) ranges from 108 to 127 °C, whereas the crystalline temperature ranges from 63 to 108 (J g −1 ). In the E–ENB copolymers, the value of k p E is much greater than that of k p ENB; at 120 s, the k p E and k p ENB values are 9115 and 431 L mol −1 s −1, respectively, implying smaller diffusion barriers in the early stages, which are close to the actual propagation rate constant.